2018
DOI: 10.1590/s1677-5538.ibju.2017.0464
|View full text |Cite
|
Sign up to set email alerts
|

Are uroflowmetry and post - void residual urine tests necessary in children with primary nocturnal enuresis?

Abstract: Objectives:To examine the benefits of repetitive uroflowmetry and post void residual urine (PVR) tests in children with primary nocturnal enuresis (PNE).Material and methods:Children aged ≥6 years with PNE who visited our clinics for management of enuresis were included for study. Patients were requested to complete a questionnaire including baseline characteristics and Dysfunctional Voiding Symptom Score (DVSS), 2-day bladder diary, and Rome III criteria for constipation. Two uroflowmetry and PVR tests were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Instead, they confirmed that elevated PVR and NP were significant predictors for medical treatment. 1 Beksac et al also revealed that PVR could predict treatment prognosis. 12 In this study, the response rate increased with FBC and FBC/EBC ratio, but there was no significant difference among CR, PR, and NR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Instead, they confirmed that elevated PVR and NP were significant predictors for medical treatment. 1 Beksac et al also revealed that PVR could predict treatment prognosis. 12 In this study, the response rate increased with FBC and FBC/EBC ratio, but there was no significant difference among CR, PR, and NR.…”
Section: Discussionmentioning
confidence: 99%
“…20 Thus, practical consensus guidelines for the management of NE suggest that a reduced FBC for age is associated with a lower response rate to desmopressin. 1 However, some studies reported that a small FBC was not associated with treatment response. Chang et al found no significant association between a reduced FBC and response to medical treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This questionnaire was named the DV Symptom Score (DVSS). So far, the DVSS was used in many studies for the follow-up of patients with DV, and for the estimation of treatment effectiveness [ 6 , 7 , 8 ]. It was also used in DV patients with attention-deficit or hyperactivity disorder [ 6 ].…”
Section: Introductionmentioning
confidence: 99%